2001
DOI: 10.1182/blood.v97.3.685
|View full text |Cite
|
Sign up to set email alerts
|

Hemophilia A mutations associated with 1-stage/2-stage activity discrepancy disrupt protein-protein interactions within the triplicated A domains of thrombin-activated factor VIIIa

Abstract: Thrombin-activated factor VIII (FVIIIa) is a heterotrimer with the A2 subunit (amino acid residues 373-740) in a weak ionic interaction with the A1 and A3-C1-C2 subunits. Dissociation of the A2 subunit correlates with inactivation of FVIIIa. Patients with hemophilia A have been described whose plasmas display a discrepancy between their FVIII activities, where the 1-stage activity assay displays greater activity than the 2-stage activity assay. The molecular basis for one of these mutations, ARG 531 HIS , is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(112 citation statements)
references
References 35 publications
5
107
0
Order By: Relevance
“…Several FVIII point mutations have been shown to facilitate the rate of dissociation of A2 relative to WT, and these residues localize to either the A1-A2 domain interface (23,24) or the A2-A3 domain interface (25). Previously, we reported that among several charged residues located at the interface between A1 and A2 domains or between A2 and A3 domains Asp-519, Glu-665, and Glu-1984 were found to be detrimental to FVIII/FVIIIa stability (20,26).…”
Section: Discussionmentioning
confidence: 99%
“…Several FVIII point mutations have been shown to facilitate the rate of dissociation of A2 relative to WT, and these residues localize to either the A1-A2 domain interface (23,24) or the A2-A3 domain interface (25). Previously, we reported that among several charged residues located at the interface between A1 and A2 domains or between A2 and A3 domains Asp-519, Glu-665, and Glu-1984 were found to be detrimental to FVIII/FVIIIa stability (20,26).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have estabilished that vWF is required for stable association of F8C heavy and light chains, efficient F8C production and protection from enzymatic degradation, for example by activated protein C and FXa. vWF also prevents F8C binding onto phospholipids (Pipe et al, 2001). Two F8C regions are involved in F8C binding to vWF: the aminoterminal region of the A3 domain and the C2 domain.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Limited information is available regarding the association of the A2 subunit in factor VIIIa, and residues in both the A1 and A3 domains appear to make contributions to the retention of this subunit. Several factor VIII point mutations have been shown to facilitate the dissociation of A2 relative to wild type (WT), and these residues localize to either the A1-A2 domain interface 14,15 or the A2-A3 domain interface. 16 These factor VIII variants demonstrate a characteristic 1-stage/2-stage assay discrepancy, 17,18 with significant reductions in activity values determined by the latter assay as a result of increased rates of A2 subunit dissociation.…”
Section: Introductionmentioning
confidence: 99%